2014
DOI: 10.1128/mbio.02158-14
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Phylogenetic Reconstruction from Whole Genomes Is Robust to Recombination but Demographic Inference Is Not

Abstract: Phylogenetic inference in bacterial genomics is fundamental to understanding problems such as population history, antimicrobial resistance, and transmission dynamics. The field has been plagued by an apparent state of contradiction since the distorting effects of recombination on phylogeny were discovered more than a decade ago. Researchers persist with detailed phylogenetic analyses while simultaneously acknowledging that recombination seriously misleads inference of population dynamics and selection. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 25 publications
4
100
2
Order By: Relevance
“…It has previously been shown that in maximum likelihood analyses of concatenated alignments, HGT influences branch lengths but hardly affects the topology of the resulting tree2324. The resulting rooted tree topology thus represents vertical inheritance among the 53 E. coli strains.…”
Section: Resultsmentioning
confidence: 98%
“…It has previously been shown that in maximum likelihood analyses of concatenated alignments, HGT influences branch lengths but hardly affects the topology of the resulting tree2324. The resulting rooted tree topology thus represents vertical inheritance among the 53 E. coli strains.…”
Section: Resultsmentioning
confidence: 98%
“…Recombination has also long been known to occur in some large DNA viruses, such as poxviruses, and whole-genome sequencing is providing new opportunities to shed light on its frequency and genomic consequences [52]. Ignoring recombination when analysing measurably evolving pathogens can be misleading [53], but accounting for such a complex and variable process is difficult. If all the strains under study are closely related, for example when studying a local outbreak, then most recombination among them will have little effect compared to imported sequences from other lineages, which would introduce a relatively high number of nucleotide changes.…”
Section: Biological Complexitiesmentioning
confidence: 99%
“…SNPs can be introduced into bacterial genomes individually via mutations or in clusters by recombination, a process that may bias demographic inferences and rate estimates (Hedge & Wilson, 2014;Lapierre et al, 2016). In particular, ignoring recombination can lead to incorrect estimates of branch lengths, which in turn results in an apparently overdispersed molecular clock, precluding accurate estimates of evolutionary rates and time-scales.…”
Section: Impact Statementmentioning
confidence: 99%